Using Plasma TiO—Polyethylene Composites for Removing Cr(VI) - G. García-Rosales; F. González-Salgado; M.G. Olayo; G.J. Cruz (Adsorption Science & Technology)
Composite particles were synthesized using titanium oxide attached to polyethylene (TiO x –PE) films by plasma techniques and used for the removal of Cr(VI) from aqueous solutions in batch systems. The precursor to synthesize TiO was titanium tetrapropoxide (TTP) modified by collisions with accelerated particles in the plasma of water in order to separate the fractions of organic and inorganic TTPs that reorganize into small organometallic particles attached to the surface of PE. Before adsorption, the TiO x particles have spherical profiles agglomerated on the PE surface. The diameter was between 70 and 120 nm in agglomerates of around 500 nm; however, as the pH of the Cr solutions increased, the morphology of these particles changed to fibred patterns. The specific surface area was 163 m 2 /g, which is greater than that for commercial TiO 2 and the pore size was 2.86 nm with a pore density of 0.11 cm 3 g −1 . The study results showed that the maximum Cr adsorption capacity (5.32 mg g −1 ) was obtained at pH = 3. The retention rate of Cr in the first minute was approximately 23%, and after 40 minutes, the rate reached up to 75%. During the adsorption process, a strong pH-dependent adsorption as a function of pH was observed. The adsorption kinetics of the TiO x –PE composites was studied using a pseudo-second-order model. The Cr(VI) experimental isotherm data were described by the Langmuir model.